2010
DOI: 10.1111/j.1471-0528.2010.02651.x
|View full text |Cite
|
Sign up to set email alerts
|

The multidisciplinary colposcopy meeting: recommendations for future service provision and an analysis of clinical decision making

Abstract: Methods Retrospective review of the colposcopy database (Sept 2003-Sept 2009, cross-referenced with multidisciplinary team (MDT) letters, patient notes and the hospital results reporting system. Baseline statistics were used for data analysis.Main outcome measures Indications for MDT referral; concordance rates from cytopathology and histopathology review; concordance rates between MDT treatment decisions and final patient management.Results A total of 535 cases were discussed at 62 MDT meetings during the all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
3
13
1
Order By: Relevance
“…To reduce the emotional burden of decision-making, health care providers will defer decision-making [ 47 ] and the majority of our participants felt a reduction in emotional burden following an MDT decision to offer excision, particularly in young and/or nulliparous women. This finding is supported by studies which have shown that the use of the MDT reduces overtreatment in the colposcopy setting [ 48 ] and potential heterogeneity in care. Although it should be noted, that with a paucity of evidence to guide this expert body’s management, homogeneity of care may be achieved within departments or regions but may not occur at a national level.…”
Section: Discussionsupporting
confidence: 56%
“…To reduce the emotional burden of decision-making, health care providers will defer decision-making [ 47 ] and the majority of our participants felt a reduction in emotional burden following an MDT decision to offer excision, particularly in young and/or nulliparous women. This finding is supported by studies which have shown that the use of the MDT reduces overtreatment in the colposcopy setting [ 48 ] and potential heterogeneity in care. Although it should be noted, that with a paucity of evidence to guide this expert body’s management, homogeneity of care may be achieved within departments or regions but may not occur at a national level.…”
Section: Discussionsupporting
confidence: 56%
“…The introduction of HPV primary screening has increased the proportion of women reviewed in colposcopy 10 and the outcomes of current studies may affect future recommendations for national [11][12][13][14][15] Current NHS CSP guidance recommends colposcopy and appropriate biopsy. In the USA, colposcopy with endocervical sampling is recommended for all women with glandular changes on cytology, irrespective of the grade.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evidence discussed, it is the authors' opinion that in the presence of normal colposcopy and a normal diagnostic biopsy, efforts be made to rule out endometrial pathology and these women should be discussed at the local MDT meeting, as per BAC guidance. 9,15 In women >40 years or those with risk factors such as obesity or diabetes, an endometrial pipelle would appear prudent. This is particularly important as the prevalence of endometrial hyperplasia and adenocarcinoma is increasing in the UK, in line with the rise in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…This Multidisciplinary Meeting (MDM) became a focal point to discuss cases by different professionals with the ultimate goal to establish a consensus on the diagnosis and the optimization of the patients' treatment (Kane and Luz, 2009). These clinical meetings can be used either for the education of patients (Rosen et al, 1998;Wilson et al, 2007;Burton et al, 2009;Ortega-Solano et al, 2011) or the evaluation and treatment of patients (Cook et al, 1996;Howard et al, 1997;Wright et al, 2009;Palmer et al, 2010;Moss, 2010;Roffey et al, 2011); so somebody could say they are service meetings.…”
Section: Introductionmentioning
confidence: 99%